2015
DOI: 10.1016/j.drugalcdep.2015.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among heroin users and users of other internationally regulated drugs: A 27-year follow-up of users in the Epidemiologic Catchment Area Program household samples

Abstract: Background In contrast to research on more restricted samples of drug users, epidemiological studies open up a view of death rates and survivorship of those who have tried heroin a few times, with no acceleration toward sustained use patterns often seen in treatment and criminal justice samples. At their best, epidemiological estimates of heroin effects on risk of dying are not subject to serious selection biases faced with more restricted samples. Methods Data are from 7207 adult participants aged 18–48 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…Based on the findings, most of the drug addicts in Terengganu were formerly school student (from primary school and secondary school). This result supported by research from [37] which found that more than 70% of drug addicts started using drugs at the age of 10-20 years old. Furthermore, [38] reported that some causes of drug abuse among children and adolescent include a lack of knowledge, having appropriate attitudes about illegal drugs and lack of skills to prevent themselves from becoming addicted to drugs, peer pressure, emotional immaturity and lack of self-esteem.…”
Section: B Clusters Of Drug Addicted Person's Socioeconomic Statussupporting
confidence: 65%
“…Based on the findings, most of the drug addicts in Terengganu were formerly school student (from primary school and secondary school). This result supported by research from [37] which found that more than 70% of drug addicts started using drugs at the age of 10-20 years old. Furthermore, [38] reported that some causes of drug abuse among children and adolescent include a lack of knowledge, having appropriate attitudes about illegal drugs and lack of skills to prevent themselves from becoming addicted to drugs, peer pressure, emotional immaturity and lack of self-esteem.…”
Section: B Clusters Of Drug Addicted Person's Socioeconomic Statussupporting
confidence: 65%
“…In this study’s analyses, these post-baseline AUD cases are included in the subgroup of individuals with no AUD, and those with post-baseline drunkenness are counted in the ‘never drunk’ subgroup at baseline. Lopez-Quintero and colleagues (2015) have mentioned this type of scenario as a ‘Len Bias’ bias that must be faced in prospective cohort studies of alcohol and other drug-related mortality unless there is continuous time surveillance and monitoring of the alcohol and other drug exposures throughout the follow-up interval. Because continuous time surveillance and monitoring of alcohol and other drug exposures may never be achieved in prospective studies of long duration, we judge this caution as one that will apply generally in studies of drunkenness and AUD-associated mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Epidemiologic Catchment Area (ECA) study, Eaton and colleagues (2013) found that both drug and alcohol abuse and dependence are associated with elevated mortality risk. Another study that used ECA data demonstrated that heroin use, including infrequent use, was associated with about a 3.5 fold excess risk of mortality, with the cause of death most commonly due to infections or injury (Lopez-Quintero et al, 2015). In two population-based studies, cocaine (Muhuri and Gfroerer, 2011; Qureshi et al, 2014) or heroin use (Muhuri and Gfroerer, 2011) were associated with elevated mortality risk; although, in one study, the association between cocaine use and mortality was no longer significant once the model adjusted for socioeconomic status, cigarette use, and alcohol use (Muhuri and Gfroerer, 2011).…”
Section: Introductionmentioning
confidence: 99%